The Development of Critical Thinking Assessment Instruments on Thematic Learning of Life Events in the Fifth Class of Elementary School Students - Anggi Pradita; Sahyar Sahyar; Siman Siman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to: (1) investigate the feasibility level of developing a critical thinking assessment instrument in the fifth grade thematic lesson of state primary school number 107396 Paluh Merbau, (2) find out the level of effectiveness of critical thinking assessment in the fifth grade thematic lessons at the school, and (3) find out the practicality level of the assessment instrument for critical thinking in the fifth grade. The subject in this study is students of class V state primary school number 107396 Paluh Merbau and the object in this study is the developed critical thinking instruments. The data collection instruments used consisted of learning outcomes test and observation. The results show that the product of this critical thinking assessment instrument is validated by three expert evaluation lecturers who have expertise in their fields. The results of the analysis on three aspects of the evaluation expert are the aspect of content feasibility before the revision received a score of 95% with the criteria very feasible. In the construction aspect, it obtains a score of 87.50% with the criteria very feasible and the linguistic aspect obtains a score of 79, 16% with the feasible criteria. The product of critical thinking assessment-based test instruments for mapping primary school student learning outcomes on cognitive competencies is able to facilitate and benefit teachers in conducting assessments. It is in line with the formulation of the problem which states that critical thinking assessment-based test instruments are for mapping student learning outcomes in effective critical thinking used by the teacher in assessing students' critical thinking assessment.